Protocol for the melatools skin self-monitoring trial: a phase II randomised controlled trial of an intervention for primary care patients at higher risk of melanoma. Issue 11 (28th November 2017) - Mills, Katie; Emery, Jon; Lantaff, Rebecca; Radford, Michael; Pannebakker, Merel; Hall, Per; Burrows, Nigel; Williams, Kate; Saunders, Catherine L; Murchie, Peter; Walter, Fiona M
Abstract : Introduction: Melanoma is the fifth most common cancer in the UK. Incidence rates have quadrupled over the last 30 years and continue to rise, especially among younger people. As routine screening of the general population is not currently recommended in the UK, a focus on secondary prevention through early detection and prompt treatment in individuals at increased risk of melanoma could make an important contribution to improve melanoma outcomes. This paper describes the protocol for a phase II, multisite, randomised controlled trial, in the primary care setting, for patients at increased risk of melanoma. A skin self-monitoring (SSM) smartphone 'App' was used to improve symptom appraisal and encourage help seeking in primary care, thereby promoting early presentation with skin changes suspicious of melanoma. Methods and analysis: We aim to recruit 200 participants from general practice waiting rooms in the East of England. Eligible patients are those identified at higher melanoma risk (using a real-time risk assessment tool), without a personal history of melanoma, aged 18 to 75 years. Participants will be invited to a primary care nurse consultation, and randomised to the intervention group (standard written advice on skin cancer detection and sun protection, loading of an SSM 'App' onto the participant's smartphone and instructions on use including self-monitoring reminders) or control group (standard written advice alone). The primary outcomes are consultation rates for changes to a pigmented skin lesion, and the patient interval (time from first noticing a skin change to consultation). Secondary outcomes include patient sun protection behaviours, psychosocial outcomes, and measures of trial feasibility and acceptability. Ethics and dissemination: NHS ethical approval has been obtained from Cambridgeshire and Hertfordshire research ethics committee (REC reference 16/EE/0248). The findings from the MelaTools SSM Trial will be disseminated widely through peer-reviewed publications and scientific conferences. Trial registration number: ISCTRN16061621.